PERBUATAN MELAWAN HUKUM MATERIL TERHADAP TINDAKAN MENGAMBIL BRONDOLAN SAWIT (STUDI KASUS KABUPATEN NAGAN RAYA DESA LAMIE) - Muhammad Ikhwan Adabi; Chandra Darussman S; Apri Rotin Djusfi; Phoenna Ath Thariq; Eza Aulia; Jalaluddin Jalaluddin (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
An act against the material law in criminal law is that a person commits an act against the law living in society (unwritten law). So if a person's actions are not against an unwritten law, then he cannot be punished. The author wants to investigate whether the theft of loose palm oil in Lamie Village is an act against the law or not. The author's initial hypothesis is that in several plantations in Lamie Village, after harvest workers have finished harvesting palm oil where they work, there is a habit of harvesting workers choosing loose palm kernels that have fallen to the ground and then sold. The research method in this writing is through an empirical juridical approach. This research was conducted by enforcing or applying normative law into legal relationships in society. The results of the study said that all garden owners in Lamie Village with a land area of 3 ha and above allowed harvesters to take loose palm oil. So the harvester's actions are not against the unwritten law. Then, some garden owners whose land area is 3 ha and below must have prior permission from the garden owner. If the permit is given then it does not violate the unwritten law, but on the contrary if the permission is not given then the perpetrator may be subject to Article 362 of the Criminal Code concerning theft.